Statistical optimisation of used-cooking-oil degradation by Burkholderia vietnamiensis AG5-12 and Burkholderia SP. AG5-13 - Ahmed, Mariyam Shabeena; Ahmad, Siti Aqlima; Shukor, Mohd Yunus; Yusof, Mohd Termizi (Multidisciplinary Digital Publishing Institute, 2022)
Used cooking oil (UCO) is a hydrocarbon that causes significant environmental pollution globally. Oil is a difficult pollutant to remove from the environment due to its hydrophobic nature. Bioremediation is preferred over chemical and physical remediation approaches as it is more economical and environmentally friendly. Hence, the search for a microbe with outstanding degrading capability is imperative due to the nature of hydrocarbons as pollutants. The current study evaluates the ability of glyphosate degrader isolates, Burkholderia vietnamiensis AQ5-12 and Burkholderia sp. AQ5-13, to degrade UCO as the sole carbon source. The physico-cultural conditions affecting the activities of the isolates were studied using one-factor-at-a-time (OFAT) and response-surface methodology (RSM). The temperature, agitation speed, UCO concentration, nitrogen supply, yeast extract concentration, and inoculum size were optimised during a 7-day incubation period. Based on the OFAT results, the highest degradations were 62.23% and 58.33% for the isolates AQ5-12 and AQ5-13, respectively. The optimisation of RSM showed 83.42% and 87.09% degradation of the UCO by the AQ5-12 and AQ5-13 isolates. Parameters including the temperature, yeast extract, and ammonium sulphate concentration provided significant interaction for the RSM model in the isolate AQ5-12. Meanwhile, AQ5-13 showed significance in all five parameters: pH, UCO concentration, temperature, yeast extract, and ammonium sulphate concentration. The degradation efficiency validated via RSM demonstrated better results than the OFAT approach. The model validation has verified no significant difference between the experimental and predicted values. The ability of these two bacterial isolates to degrade UCO is a worthwhile procedure in the bioremediation of hydrocarbon-rich areas.